PENGARUH METODE LATIHAN CROSSBAR DAN CROSSING TERHADAP HASIL LONG PASS PADA ATLET SSB PERSETAJA USIA 15-25 SIMALUNGUN - Mahmuddin; Septian, Abdi (JURNAL ILMU KEOLAHRAGAAN, 2024)
This study aims to determine the effect of Crossbar and Crossing training methods on the results of long passes made by SSB PERSETAJA athletes in 2024 in the game of football. The research method used is the experimental method and the research design used is One- Groups Pretest - Posttest Design. The population in this study were SSB PERSETAJA athletes totalling 47 people. The sampling technique used was Purposive Sampling so that the sample in this study was 12 people. This research was conducted for 6 weeks with a frequency of training 3 times each week. The data analysis technique is to conduct a non- parametric Wilcoxon signed ranking test and hypothesis testing. From the results of hypothesis testing, it was obtained that the effect of crossbar and crossing training methods on long pass results was statistically significant for both types of Bobby Charlton tests (P value ≤ 0.05). The conclusion of this study is that there is a significant effect of crossbar and crossing training methods on the results of long pass football in athletes aged 15-25 years at SSB PERSETAJA Simalungun in 2024